2021
DOI: 10.17146/jsmi.2021.22.3.6182
|View full text |Cite
|
Sign up to set email alerts
|

THE IMPROVEMENT OF RAMIE FIBER PROPERTIES AS COMPOSITE MATERIALS USING ALKALIZATION TREATMENT: NaOH CONCENTRATION

Abstract: THE IMPROVEMENT OF RAMIE FIBER PROPERTIES AS COMPOSITE MATERIALS USING ALKALIZATION TREATMENT: NaOH CONCENTRATION. Ramie fiber is a plant fiber that has good quality and potential as a constituent of composite materials. In this study, ramie fiber surface modification was conducted through alkalization with various at 0%, 4%, 5%, 6%, 7%, 8%, and 9% concentrations of NaOH using a magnetic stirrer with a speed of 200 rpm at 70οC for 5 hours. Alkaline ramie fibers are characterized using the Cheson method to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The physique properties such as suspension's characteristics of the ramie fibres are influenced by the sodium hydroxide (NaOH) concentration [16]. One of the factors showing the stability of suspension is dispersion stability.…”
Section: Resultsmentioning
confidence: 99%
“…The physique properties such as suspension's characteristics of the ramie fibres are influenced by the sodium hydroxide (NaOH) concentration [16]. One of the factors showing the stability of suspension is dispersion stability.…”
Section: Resultsmentioning
confidence: 99%
“…0 (10) where the coefficient k is the value of thermal conductivity, Ro is the rate at which the ice melts, h is the thickness of the sample, A is the surface area of the sample, while ΔT is the temperature difference.…”
Section: Resultsmentioning
confidence: 99%
“…From the test, it was found that the maximum average tensile strength of 57.37 MPa was obtained in the fibres that were given alkaline treatment with 8% NaOH, while after being given alkaline treatment with 9% NaOH, the average tensile strength tended to decrease to 41.19 MPa. The decrease in fibre strength could be caused by damage to the fibre structure due to an excessive amount of NaOH concentration, so it is necessary to know the exact concentration to obtain the optimum result [10] .…”
Section: Pure Iron 73mentioning
confidence: 99%
“…Graphene with 98% purity, 10-15 layers, 10-15 micron diameter and 10-15 nm thickness is procured from Shilpa enterprises, Maharashtra, India. The fiber is subjected to chemical treatment by soaking it in 5% diluted NaOH solution for 4 h [23] and it is dried at room temperature for 24 h to break the hydrogen bonds [24]. The NaOH-treated fiber is washed with distilled water to remove the excess NaOH present in the fiber and dried again for a day at 40 °C in a hot air oven.…”
Section: Materials and Fiber Chemical Treatmentmentioning
confidence: 99%